The Influence of Applying the Imtihan Method in Learning to Memorize the Al-Quran on the Self-Confidence of TPQ Al-Huda Karawang Students - Fariha Hidni Salama; Iwan Hermawan; Nur Aini Farida (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Self-confidence is the key to meeting various life needs. phenomena that occur during the learning process, not all students have high self-confidence, and lack of self-confidence are symptoms that are often experienced by children. Efforts that can help to overcome these problems, such as in an educational environment, exercises are held in the form of evaluations to measure the abilities or success of students,one form of evaluation is the imtihan method (oral exam). The aim of this research is to find out how the imtihan method is applied in tpq al-huda, and the reality of students' self-confidence in tpq al-huda as well as the influence of the application of the imtihan method on students' self-confidence. The method used is a quantitative method with an ex post facto type of research. This method is used to discover what causes changes in behavior, symptoms, or phenomena caused by an event. Then data retrieval is used with observation, cassette and documentation. test results for constants and coefficients of the linear regression equation Y = 39,453 + 0.262 X. From the significant test results, a significant value of 0.000 was obtained. Significance value < 0.05 (0.000 < 0.05), then Ha is accepted, so it can be interpreted that “the application of the imtihan method in learning to memorize the Koran has a significant effect on the self-confidence of TPQ Al-Huda Karawang students. The level of influence of the application of the imtihan method on the self-confidence of TPQ Al-Huda students contributed 47.2%.